GEOPOLITICAL ISSUE ANALYSIS OF THE RUSSIA - UKRAINE WAR FROM AN INTERNATIONAL POLITICAL ECONOMY PERSPECTIVE AND ITS IMPLICATIONS FOR AUSTRALIA - Indrayani, Irma; Nurhadi, Robi; Putri, Ni Luh Pingkan Amalia Pratama (Journal of Social Political Sciences, 2024)
The invasion of Ukraine by Russia has become a critical point of international discourse, significantly affecting global stability and reshaping regional security dynamics. This paper analyzes the conflict through a geopolitical lens, focusing on its historical context, strategic implications, and global impact, with particular attention to Australia. The study traces the complex Russia-Ukraine relationship from the Soviet era to the present, highlighting the historical factors that have shaped their actions, responses, and global consequences. The paper also explores the concept of hybrid warfare, examining Russia’s use of conventional and unconventional tactics, such as cyber-attacks, propaganda, and proxy forces. Furthermore, the research investigates the economic dynamics within the energy sector involving Russia, Ukraine, and the European Union, analyzing shifts in energy dependence due to regional geopolitical changes and their implications for Australia’s energy security. The economic impact of the conflict on global markets and supply chains, particularly concerning Australia, is also discussed. By employing geopolitical theory, the analysis delves into the motivations behind Russia’s actions and the subsequent international response, including Australia’s strategic positioning and defense considerations. The paper concludes that the Russia-Ukraine conflict marks a significant shift in global power dynamics, presents new challenges to traditional security frameworks, and underscores the need to reevaluate international norms and alliances. This study emphasizes the complexity of modern conflicts that intertwine military, economic, and information warfare, and advocates for a redefined international relations landscape to address the challenges of the 21st century, with a focus on Australia’s role in these developments.